Graph Drawing 19th International Symposium, GD 2011, Eindhoven, The Netherlands, September 21-23, 2011, Revised Selected Papers - van Kreveld, Marc.; van Kreveld, Marc.; Speckmann, Bettina.; Speckmann, Bettina. (Theoretical Computer Science and General Issues, 2012)
This volume constitutes the refereed proceedings of the 19th International Symposium on Graph Drawing, GD 2010, held in Eindhoven, The Netherlands, during September 2011. The 34 revised full papers presented together with 3 revised short and 6 poster papers were carefully reviewed and selected from 88 submissions. Furthermore, the proceedings contain the abstracts of two invited talks and to commemorate Kozo Sugiyama and his pioneering research in graph drawing, the proceedings include an obituary. A unique and fun part of the symposium is the Graph Drawing Contest, which is part of the Graph Drawing Challenge. This year was the 18th edition. A report on the contest is included at the end of the proceedings.